FRAUD PENTAGON SEBAGAI ALAT PENDETEKSI FINANCIAL STATEMENT FRAUD : LITERATUR REVIEW - Ditya Permatasari (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to detect the possibility of fraud in the financial statements by using the fraud pentagon. The fraud pentagon is an extension of the fraud triangle and fraud diamond theory which is used to detect fraud in financial statements. The method used in this study is the Systematic Literature Review (SLR) which examines previous research on financial statement fraud and the fraud pentagon. The data used is data from a second party. Analysis of the data in this study by mapping 28 selected journals from 2017 to 2020 in the Google Scholar database. Based on the results of the research conducted, it shows the factors that influence financial statement fraud which are divided into five indicators, namely pressure, opportunity, rationalization, competence and arrogance which are then translated into several proxies with quantitative research types. The factor that is widely studied is the change in director as much as 27 times. But for the factors that have a lot of influence on the occurrence of financial statement fraud is financial stability (financial stability). This means that when the company's financial stability is threatened due to economic and industrial factors, the company will have the potential to commit financial statement fraud.